2015
DOI: 10.15252/emmm.201505444
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of the Cullin‐3 mutation that causes a severe form of familial hypertension and hyperkalaemia

Abstract: Deletion of exon 9 from Cullin-3 (CUL3, residues 403–459: CUL3Δ403–459) causes pseudohypoaldosteronism type IIE (PHA2E), a severe form of familial hyperkalaemia and hypertension (FHHt). CUL3 binds the RING protein RBX1 and various substrate adaptors to form Cullin-RING-ubiquitin-ligase complexes. Bound to KLHL3, CUL3-RBX1 ubiquitylates WNK kinases, promoting their ubiquitin-mediated proteasomal degradation. Since WNK kinases activate Na/Cl co-transporters to promote salt retention, CUL3 regulates blood pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
165
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 82 publications
(185 citation statements)
references
References 77 publications
(124 reference statements)
20
165
0
Order By: Relevance
“…The Sigmund group reported that WT CUL3/CUL3-Δ9 heterodimers are less stable than CUL3 WT/WT homodimers, and that CUL3-Δ9 may also sequester adapters (29). Finally, the Kurz group confirmed our finding with respect to inappropriate degradation of KLHL3 but also reported that CUL3-Δ9 displays autoubiquitination, leading to its own proteasomal degradation (30). A major limitation with most of these studies has been the reliance on in vitro approaches, but the Kurz group also generated a mouse model of FHHt by targeted deletion of exon 9 of the Cul3 gene.…”
Section: CLsupporting
confidence: 83%
See 4 more Smart Citations
“…The Sigmund group reported that WT CUL3/CUL3-Δ9 heterodimers are less stable than CUL3 WT/WT homodimers, and that CUL3-Δ9 may also sequester adapters (29). Finally, the Kurz group confirmed our finding with respect to inappropriate degradation of KLHL3 but also reported that CUL3-Δ9 displays autoubiquitination, leading to its own proteasomal degradation (30). A major limitation with most of these studies has been the reliance on in vitro approaches, but the Kurz group also generated a mouse model of FHHt by targeted deletion of exon 9 of the Cul3 gene.…”
Section: CLsupporting
confidence: 83%
“…CUL3-Δ9 protein was detectable in infected primary cells from CUL3-Het/Δ9 mice but not from CUL3-Het mice, with the size of CUL3-Δ9 confirmed using lysates from HEK293 cells transfected with plasmids encoding the transgene and Cre ( Figure 1F). CUL3-Δ9 was expressed at extremely low levels, consistent with its ability to initiate its own degradation via autoubiquitination (30). CUL3 has been proposed to be activated by covalent linkage of an 81-amino acid protein Neural precursor cell expressed developmentally downregulated protein 8 (Nedd8), a process called neddylation that is specific to Cullins (35).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations